One-Year Review Of Reduced Fetal Movements In Izzat Ali Shah MCH Center: A Predictor Of Poor Perinatal Outcome - Rani, Humera; Salahuddin, Gulwish; Naz, Ayesha; Majeed, Noreen; Safdar, Faiza; Rafique, Shazia (Journal of Rawalpindi Medical College, 2023)
Objectives: To find out common causes of reduced fetal movements. The purpose is to reduce perinatal morbidity and mortality. Methodology: This Prospective, Observational study was conducted at Izzat Ali Shah Maternal and child health center, unit III Gynae, Wah medical college Wah Cantt, from January 2019 to December 2019. A total of participants 160, who presented in the antenatal outpatient or emergency department with reduced fetal movements, were included in the study. Patients in the active phase of labor were excluded from the study. Patients were followed up till delivery. All necessary information, investigations, and examination points were noted on the predesigned proforma. Data were analyzed by using SPSS version 22. Results: Out of a total of 160 patients, 144 had alive and stable babies. Regarding the age group, out of 160, six patients were teenagers (3.75%), 98 (61.25%) were between 20-30 years, and 55(34.3%) were in the age group of 30-40 years. Regarding gestational age at presentation, 27 out of 160(16.8%) were between 30-35 weeks, 133(83.12%) was at 36-40 weeks. None of the patients presented below 30 weeks. Concerning the number of pregnancy, primigravida 82(51.25%), 60(37.5%) were multigravida, and 18 (11.25%) was grand multipara. Regarding medical history, anemia was seen in 31 patients (19.37%), pregnancy-induced hypertension in 20(12.5%), and 65 %( 104) has no significant medical history. Concerning past obstetrical history, 107(66.8%) fell under low-risk pregnancies, 18(11.25%) had previously normal deliveries but 08(05%) patients had H/O still births. Regarding placental position, 71(44.37%) had anterior, 71(44.37%) had posterior, and 18 (11.25) had fundal placenta. Regarding UAD, 136(85%) had normal umbilical artery Doppler, 13(8.12%) had altered, 06(3.75%) were Absent and 05 (3.12%) has reversed end diastolic flow. During study, 78(48.7%) had normal AFI, 69(43.12%) has Oligohydramnios, 10(6.25%) anhydramnios, while only 03(1.87%) had polyhydramnios. Regarding birth weight, 122(76.25%) had average weight, 32(20%) were low birth weight and 05(3.12%) were very low birth weight. 61(38.12%) went into NICU, while 99(61.8%) no admission required. Conclusion: Most common risk factor or cause of reduced fetal movements was reduced liquor, (79). Out of which 69 remained alive and stable after birth, while 15 had early neonatal deaths. The second cause found was abnormal umbilical artery Doppler,(24). Out of which, 14 had early neonatal deaths and intrauterine deaths. This study showed the increased obligation of care required by patients with decreased fetal movement. Although the number of live births is more as compared to demise, it results in increased neonatal unit admission rates, higher induction and cesarean section rates, higher surveillance demands, and an increased financial burden on parents. It signifies the need for more vigilance in this area of practice. But we can’t neglect the perception of a mother. Mother’s feelings are more important than any other test.